Changes in left atrial function following two regimens of combined exercise training in patients with ischemic cardiomyopathy: a pilot study - Caminiti, Giuseppe; Volterrani, Maurizio; Iellamo, Ferdinando; Marazzi, Giuseppe; Manzi, Vincenzo; D’Antoni, Valentino; Vadalà, Sara; Di Biasio, Deborah; Catena, Matteo; Morsella, Valentina; Perrone, Marco Alfonso (Frontiers in Cardiovascular Medicine, 2024)
Purpose: Left atrial dysfunction has showed a prognostic role in patients with ischemic cardiomyopathy (ICMP) and is becoming a therapeutical target for pharmacological and non-pharmacological interventions. The effects of exercise training on atrial function in patients with ICMP has been poorly investigated. In the present study we assessed the effects of a 12-weeks combined exercise training (CT) program on left atrial function in patients with ICMP. Methods: We enlisted a total of 45 clinically stable patients; they were randomly assigned to one of the following three groups: fifteen to a supervised CT with low frequency sessions (two/week) (CTLF); fifteen to supervised CT with ahigh frequency sessions (three/week) (CTHF); a third group followed contemporary exercise preventive guidelines at home (control). At baseline and at 12-weeks, all patients underwent a symptoms-limited exercise test and an echocardiography. The training included aerobic continuous exercise and resistance exercise.The analysis of variance (ANOVA) was used to compare within-groups and inter-groups changes. Results: At 12-weeks, CTLF and CTHF groups showed a similar increase in the duration of ergometric test compared to control (ANOVA p <0.001). Peak atrial longitudinal strain (PALS) increased significantly in the CTHF group while it was unchanged in the CTLF and control groups (ANOVA p 0.003). Peak atrial contraction strain (PACS) presented a significant improvement in the CTHF than in CTLF and control. Left ventricular global longitudinal strain, increased significantly in both CTHF and CTLF compared to control (ANOVA p 0.017). Systolic blood pressure decreased in CTHF and CTLF while was unchanged in control. There were no side effects causing the discontinuation of the training. Conclusions: We demonstrated that a CT program effectively improved atrial function in ICMP in a dose-effect fashion. This result can help with programming exercise training in these patients.